2016
DOI: 10.1111/boc.201500104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transplanted circulating endothelial progenitor cells and platelet microparticles in atherosclerosis development

Abstract: Our results support the notion that increasing the number of circulating endothelial progenitor cells by different ways could be a promising therapeutic tool for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…The generation of experimental diet model of atherosclerosis, the source for late EPC culture For this study, 60 male Golden Syrian hamsters aged 3 months were split into: (i) hypertensive-hyperlipidaemic hamsters (HH group)obtained by administering an ordinary feed enriched in 3% cholesterol, 15% butter and 8% NaCl, for 4 months; and (ii) control hamsters (C group)healthy animals who received classical food containing 1% NaCl. [29][30][31][32][33]70,71 Both groups of animals were kept under the same housing conditions that respect their needs.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of experimental diet model of atherosclerosis, the source for late EPC culture For this study, 60 male Golden Syrian hamsters aged 3 months were split into: (i) hypertensive-hyperlipidaemic hamsters (HH group)obtained by administering an ordinary feed enriched in 3% cholesterol, 15% butter and 8% NaCl, for 4 months; and (ii) control hamsters (C group)healthy animals who received classical food containing 1% NaCl. [29][30][31][32][33]70,71 Both groups of animals were kept under the same housing conditions that respect their needs.…”
Section: Methodsmentioning
confidence: 99%
“…Platelet activation is an essential process to repair injured blood vessels, restoring blood vascular integrity, which is fundamental for the maintenance of vascular function. However, aberrant platelet activation or hyperactivation of platelets may give rise to thrombosis and result in thrombotic vascular events, including atherosclerosis, arterial thrombosis and myocardial infarction (1)(2)(3)(4)(5). Under physiological conditions, platelets circulate through vessels with an intact and healthy endothelium, remaining in an inactivated state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the relative paucity of data on the therapeutic effects of EPCs on hyperlipidaemia-associated kidney damage, prior atherosclerosis studies provide ample support for the use of EPCs in animal models of hyperlipidaemia. In a mouse model of hypertension-hypercholesterolemia, the administration of EPCs reduced hepatic lipid accumulation and consequently alleviated hypertension and dyslipidaemia [26]. In contrast, Silvestre et al found that EPC treatment aggravated the atherosclerosis burden when EPCs were transferred from young to old ApoE −/− mice [7].…”
Section: Discussionmentioning
confidence: 99%